2012
DOI: 10.1044/1058-0360(2012/11-0044)
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Visual Learning in Children With Specific Language Impairment

Abstract: Purpose According to the procedural deficit hypothesis (PDH), difficulties in the procedural learning (PL) system may contribute to the language difficulties observed in children with specific language impairment (SLI). Method Fifteen children with SLI and their typically developing (TD) peers were compared on visual PL tasks—specifically, deterministic serial reaction time (SRT) tasks. In the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 53 publications
7
39
1
4
Order By: Relevance
“…However, some studies report a deficit only in retention of learning, not in initial sequence learning [e.g., Desmottes, Maillart, & Meulemans, 2017; Hedenius et al, 2011]. Furthermore, a substantial number of other studies have also reported comparable learning in SLI on the SRT task [Gabriel et al, 2011; Gabriel, Meulemans, Parisse, & Maillart, 2015; Gabriel, Stefaniak, Maillart, Schmitz, & Meulemans, 2012; Lum & Bleses, 2012]. The current findings also suggest that overall responses might be slower is SLI compared to ASD, and variance in the response times seems to be high.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies report a deficit only in retention of learning, not in initial sequence learning [e.g., Desmottes, Maillart, & Meulemans, 2017; Hedenius et al, 2011]. Furthermore, a substantial number of other studies have also reported comparable learning in SLI on the SRT task [Gabriel et al, 2011; Gabriel, Meulemans, Parisse, & Maillart, 2015; Gabriel, Stefaniak, Maillart, Schmitz, & Meulemans, 2012; Lum & Bleses, 2012]. The current findings also suggest that overall responses might be slower is SLI compared to ASD, and variance in the response times seems to be high.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been suggested by several authors (Gheysen et al, 2011; and seemed to receive support from some studies which have shown that a dysfunction of brain structures (such as the cerebellum and basal ganglia) which are heavily involved in the acquisition of motor skills might be involved in the pathogenesis of DCD. More specifically, we compared the performance of children with and without DCD on a variant of the Serial Reaction Time task (Gabriel et al, 2012) that reduces the potential impact of perceptuomotor coordination difficulties on the SRT performance of children with DCD. The logic for this choice was that the deficits displayed by DCD children in the SRT task might be caused by motor and cognitive deficits associated with this disorder, and not by an inability to learn sequential information per se.…”
Section: Discussionmentioning
confidence: 99%
“…As described by Gabriel, Stefaniak, Maillart, Schmitz, and Meulemans (2012), performance on an SRT task can be affected by deficits in manual dexterity and/or by difficulties matching the location of the target on the screen to the corresponding key. These cognitive and perceptuomotor constraints may affect specific-sequence learning.…”
Section: Intact Procedural Motor Sequence Learningmentioning
confidence: 99%
See 2 more Smart Citations